SHIP COLLISIONS ANALYSIS OF BOW OFFSHORE SUPPLY VESSEL (OSV) WITH MIDSHIP HULL OF 3500 DWT TANKER SHIP WITH FINITE ELEMENT METHOD - Baihaki, Iqbal
Ship collisions are accidents with significant impacts on safety, security, and the economy, in that case further study need to proceed to minimize potential consequences. The use of high-grade steel materials is relatively uncommon in ship construction due to their high cost and the limited knowledge of their effects. Numerous analysis of steel material grades on stiffened plates, such as those in ships, have been conducted using various methods, including experimental and numerical approaches. However, studies involving variations in steel material grades on ship collision phenomena are still rare, mainly because experimental methods are prohibitively expensive. In this thesis, a ship collision analysis is conducted using the Finite Element Method (FEM), a more cost-effective approach, to investigate the influence of steel material grade variations and ship collision angles on ultimate strength, structural response in terms of deformation, strain energy curves, and ship movement. The research results indicate that variations in steel material grades and collision angles significantly affect the structural response of the ship. The ultimate strength from stress-strain curves shows marked differences across various steel material grades. Additionally, structural deformation, strain energy curves, and ship motion during the collision also exhibit significant changes based on the steel material grade variations. These findings are expected to contribute to the development of ship design from a structural perspective, providing considerations for the use of specific steel material grades to mitigate the impact of ship collision accidents.